Gene-based analysis of the fibroblast growth factor receptor signaling pathway in relation to breast cancer in African American women: the AMBER consortium - Ruiz-Narváez, Edward A. (Breast Cancer Res Treat, 2016)
PURPOSE: We conducted gene-based analysis in 26 genes in the FGFR signaling pathway to identify genes carrying genetic variation affecting risk of breast cancer and the specific estrogen receptor (ER) subtypes. METHODS: Tagging single nucleotide polymorphisms (SNPs) for each gene were selected and genotyped on a customized Illumina Exome Array. Imputation was carried out using 1000 Genomes haplotypes. The analysis included 3,237 SNPs in 3,663 breast cancer cases (including 1,983 ER positive, and 1,098 ER-negative and 4,687 controls from the African American Breast Cancer Epidemiology and Risk consortium, a collaborative project of four large studies of breast cancer in African American women (Carolina Breast Cancer Study, Black Women's Health Study, Women's Circle of Health Study, and Multiethnic Cohort). We used a multi-locus adaptive joint (AdaJoint) test to determine the association of each gene in the FGFR signaling pathway with overall breast cancer and ER subtypes. RESULTS: The FGF1 gene was significantly associated with risk of ER negative breast cancer (P = 0.001). The FGFR2 gene was associated with risk of overall breast cancer (P = 0.002) and ER positive breast cancer (P = 0.002). CONCLUSIONS: The FGF1 gene affects risk of ER negative breast cancer in African American women. We confirmed the association of the FGFR2 gene with risk of overall and ER positive breast cancer. These results highlight the importance of the FGFR signaling pathway in the pathogenesis of breast cancer, and suggest that different genes in the same pathway may be associated with different ER breast cancer subtypes.